2023
DOI: 10.1155/2023/8003821
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial-Based bFGF Delivery for Nerve Repair

Abstract: Diseases in the nervous system are common in the human body. People have to suffer a great burden due to huge economic costs and poor prognosis of the diseases. Many treatment modalities are now available that can make recovery better. Managing nutritional factors is also helpful for such diseases. The basic fibroblast growth factor (bFGF) is one of the major nutritional factors, which plays a crucial role in organogenesis and tissue homeostasis. It plays a role in cell proliferation, migration, and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
0
0
0
Order By: Relevance
“…Zaia et al demonstrated that retrograde transduction of bFGF post-duct de-ligation stimulates acinar and ductal cell proliferation, promoting regeneration in rat SMG ( Okazaki, et al, 2000 ). bFGF is a highly bioactive peptide growth factor that promotes cell proliferation in the G0 and G1 phases ( Liu, et al, 2021 ; Huang, et al, 2023 ). Furthermore, the EGF signaling pathway has been shown to be activated during gland regeneration; the SMG is considered the most important organ for circulating EGF production ( Tsutsumi, et al, 1986 ; Cho, et al, 2021 ).…”
Section: Salivary Gland Duct De-ligationmentioning
confidence: 99%
“…Zaia et al demonstrated that retrograde transduction of bFGF post-duct de-ligation stimulates acinar and ductal cell proliferation, promoting regeneration in rat SMG ( Okazaki, et al, 2000 ). bFGF is a highly bioactive peptide growth factor that promotes cell proliferation in the G0 and G1 phases ( Liu, et al, 2021 ; Huang, et al, 2023 ). Furthermore, the EGF signaling pathway has been shown to be activated during gland regeneration; the SMG is considered the most important organ for circulating EGF production ( Tsutsumi, et al, 1986 ; Cho, et al, 2021 ).…”
Section: Salivary Gland Duct De-ligationmentioning
confidence: 99%